Exploring Strategies to Retain Key Employees in Star-Rated Hotels - Manuaba, Ida Bagus Purwa Arsha; Martini, Ida Ayu Oka (Jurnal Ilmiah Global Education, 2025)
Key employees are often viewed as essential assets that are critical for a company to maintain its edge and competitiveness in the face of competition with other organizations. These employees play a significant role in boosting the organization's knowledge and intellectual capital, as well as ensuring stability and continuity due to their highly specialized skills and experience in their respective fields. This study, guided by the Stimulus-Organism-Response (SOR) theory, seeks to explore the strategies employed by the management of Hotel Sankara Ubud Bali to retain its key employees. These key employees are characterized by their unique and specialized skills and knowledge, which are crucial for the organization's success. The research employs a qualitative approach and a case study method. Findings from semi-structured interviews with key employees and a general manager reveal the important roles and challenges faced by key employees at Hotel Sankara Bali. These roles include human resource management, maintenance, marketing, and innovation for business advantage. Effective strategies for retaining key employees, as perceived by both managers and the employees themselves, include sufficient social support, employee development programs, a high level of job responsibility, and a transformational leadership style. The study's implications assist hotel management in crafting the most effective strategies to improve performance and retain key employees within the company.